SOCIAL INFORMATION PROCESSING DI FACEBOOK UNTUK PENGEMBANGAN KOMUNITAS SOCIAL ENTREPRENEURS - Diah Ajeng Purwani; Partini Partini; Sri Peni W (Jurnal Ilmu Komunikasi Acta Diurna, 2018)
This study aims to reveal how the tendency of social business players to follow the trend for growingtheir business. The research method used in this research is semi-ethnography approach which will beanalyzed qualitatively. This research took the figures of youth social business in Yogyakarta whosurvived more than 3 years and use social media as one means of empowerment. In the data collection,researchers used in-depth interviews, field observations to the grouping of data through the internet.The results show that in the last three years, young social entrepreneurs more often use facebook andinstagram than other social media to develop social communities and business entrepreneurs.